2014
DOI: 10.1186/1471-2261-14-142
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent association between coronary vessel dominance and cardiac syndrome X: a case-control study

Abstract: BackgroundPrevious studies have demonstrated the relevance of left coronary artery dominance in the outcome and prognosis of obstructive coronary artery disease (CAD). However, no studies have investigated the influence of coronary vessel dominance on non obstructive CAD. The aim of this study was to establish the association of left and mixed dominance of the major epicardial arteries with the development of non obstructive CAD and evaluate potential sex-dependent differences in the coronary artery supply.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The pattern of coronary artery dominance was diagnosed according to whether the PDA originates from the RCA, LCx, or both sides, using CAG or computed tomography coronary angiography [26]. The proportion of right, left, and balanced dominance has been reported to be 70–86%, 8–13%, and 4–18%, respectively [8, 25, 27, 28]. In the present study, right dominance (94.0% vs. 87.9%), left dominance (4.5% vs. 8.1%), and co-dominance (1.5% vs. 4.0%) were statistically different between patients with acute inferior MI and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of coronary artery dominance was diagnosed according to whether the PDA originates from the RCA, LCx, or both sides, using CAG or computed tomography coronary angiography [26]. The proportion of right, left, and balanced dominance has been reported to be 70–86%, 8–13%, and 4–18%, respectively [8, 25, 27, 28]. In the present study, right dominance (94.0% vs. 87.9%), left dominance (4.5% vs. 8.1%), and co-dominance (1.5% vs. 4.0%) were statistically different between patients with acute inferior MI and the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Bizim çalışmamızda cinsiyet ile el tercihi arasında anlamlı ilişki saptanmamıştır. Koroner dominans ve cinsiyet arasında diğer çalışmalardakine benzer olarak bizim çalışmamımzda da istatiksel olarak anlamlı bir ilişki yoktur (16).…”
Section: Bulgularunclassified
“…Based on the results of our recently published research ( 24 ), we propose a new mechanism that could be added to endothelial independent mechanisms within the ischemic hypothesis on the development of non-CAD. Alongside the known endothelial independent pathophysiological mechanisms such as aortic pressure, myocardial contractility, myocardial metabolism and neurohumoral factors ( 25 ), another possible contributor would be the type of coronary supply, specifically the left type of dominance (particularly in women), and absence of mixed type in men ( 24 ).…”
Section: Nonobstructive Coronary Artery Disease – Pathophysiological mentioning
confidence: 99%
“…Non-ischemic hypothesis explains the CSX phenomenon and non-CAD because of altered pain perception ( 25 ). Previous studies demonstrated that patients with angina and normal coronary arteries had enhanced pain perception to heat and electrical stimuli ( 26 ).…”
Section: Nonobstructive Coronary Artery Disease – Pathophysiological mentioning
confidence: 99%
See 1 more Smart Citation